Pulmonary function and quality of life in patients with morbid obesity six months after bariatric surgery - Xavier,Márcia Arruda Fajardo (2010)
PURPOSE: To investigate the body weight, pulmonary function and quality of life of twenty patients with morbid obesity six months after the Fobi-Capella operation. METHODS: Patients were evaluated before and six months after surgery. The patients were mainly female (75%), the average age was 40.5 ± 10.27 years; average weight 110.11 kg ± 21.77 and average body mass index (BMI) 39.93 ± 7.13 kg/m² in the postoperative evaluation. Pulmonary function was assessed by spirometry using a Pulmonet/Godart NV Bilt Vetr Hotland spirometer and quality of life was assessed by applying the Moorehead-Ardelt questionnaire. The pre- and postoperative spirometry values were compared by the paired Student t test and the correlation between weight loss and pulmonary function was determined by linear regression, with the level of significance set at p < 0.05. RESULTS: The spirometry variables Respiratory Frequency (RF), Expiratory Reserve Volume (ERV) and Functional Residual Capacity (FRC) differed significantly between the pre- and postoperative periods, whereas Residual Volume (RV), Vital Capacity (VC), Total Lung Capacity (TLC), FEF25-75 (Forced Expiratory Flow between 25 and 75% FVC) and FEV1/FVC% (Forced Expiratory Volume in the 1st second/ Forced Vital Capacity ratio) did not differ between periods. Only one patient reported worsening of quality of life. There was a positive correlation between weight loss and ERV (p=0.0117, r=0.5514), but no correlations were observed for the other variables. CONCLUSIONS: There was a significant weight loss and an improvement of pulmonary function as seen by respiratory frequency, reduction and increased expiratory reserve volume and functional residual capacity. The quality of life of the patients also improved after the Fobi-Capella operation.